A case study: Understanding bullying behaviors of young female students - Symaco, Teri Lee Pe (Animo Repository, 2017)
The purpose of this study to understand the bullying behavior among female students using the Social Learning Theory. The social learning theory of Bandura posits that people can learn a certain behavior by observing others or through modeling. He mentioned four (4) processes that should be present for successful modeling: attention; retention; replication and reinforcement . This study specifically looked into how the bullying behavior is acquired through the different processes of the Social Learning Theory. There were six (6) participants selected for this study. The participants are perceived bullies by peers and have been involved in bullying cases in school. Based from the data collected by the researcher, the aggressive behaviors displayed by the participants in school are learned in their homes, replicated and reinforced at home and in school. The researcher provided the synthesis of the needs that emerged and recommended possible interventions to address these needs.